Grounding Line Retreat and Ice Discharge Variability at Two Surging, Ice Shelf-Forming Basins of Flade Isblink Ice Cap, Northern Greenland - Möller, Marco; Friedl, Peter; Palmer, Steven J.; Marzeion, Ben (Journal of Geophysical Research F: Earth Surface, 2022)
Ice discharge from Flade Isblink ice cap (NE Greenland) maintains an ice shelf at the northwestern fringe of the ice cap. The two outlet basins feeding this ice shelf surged during the late 1990s. Ice shelves are rare in Greenland and surges of ice shelf terminating glaciers even rarer. Understanding and explaining the evolution of ice mass changes in the two basins is hampered by a lack of knowledge about processes at their grounding zones. We determined, for the first time, the grounding line locations of these basins and analyzed their variability with time. We further quantified ice discharge and its variability during the period 1988–2020. We found that the grounding lines advanced slightly between 1993 and 1999 during the glacier surges, but showed overall retreats of 2.2 ± 1.3 km in basin 2 and 2.7 ± 0.9 km in basin 3 until 2019 over retrograde sloping beds. The retreats were promoted by increasing buoyancy forces due to increasing water depth, but opposing buttressing forces of the ice shelf induced a differing response of the grounding line in the two basins. Based on the observed patterns of flow and retreat, we characterized the surges as “Svalbard-type”, modified by buttressing effects of the ice shelf. We calculated total ice discharges over the study period of 1.85 ± 1.59 Gt in basin 2 and 1.38 ± 1.22 Gt in basin 3. We observed reductions in ice discharge of at least 90% after the surges, that persisted for the remainder of the period studied.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Greenland; grounding line; ice cap; ice discharge; ice shelf